Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18535/jmscr/v5i1.159
|View full text |Cite
|
Sign up to set email alerts
|

Burden of HCV infection among pregnant women with assessment of risk factors and pregnancy outcome in HCV infected: A hospital based study from Uttarakhand

Abstract: Introduction: Hepatitis-C is a global health problem. Risk factors for HCV infection include intravenous drug use, transfusion of infected blood or blood products, unsafe therapeutic injections and surgical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…26 Another study from Uttarakhand, also reported seroprevalence of hepatitis C to be 0.89% among pregnant women. 27 Both these studies corroborate this finding. However, in contrast to this finding, a study from Sangareddy, Telangana state reported very low prevalence (0.21%) of HCV infection among pregnant women.…”
Section: Discussionsupporting
confidence: 67%
“…26 Another study from Uttarakhand, also reported seroprevalence of hepatitis C to be 0.89% among pregnant women. 27 Both these studies corroborate this finding. However, in contrast to this finding, a study from Sangareddy, Telangana state reported very low prevalence (0.21%) of HCV infection among pregnant women.…”
Section: Discussionsupporting
confidence: 67%
“…Among the risk factors studied, previous surgery and blood transfusion were found to be the important risk factors observed in 16 (25.80%) and 5 (8.06%) of anti-HCV positive pregnant women. 19 In another study 39 (0.48%) women were found to be HBsAg carriers. Furthermore, prevalence was much lower in German-born women (0.2%) in comparison to Asian-born women (9.1%) and these women with HBsAg had no significantly increased prevalence of adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 91%